Fully human anti-BAFF inhibitory monoclonal antibody tabalumab does not adversely affect T-dependent antibody responses in cynomolgus monkey (Macaca fasicularis): A summary of three pre-clinical immunotoxicology evaluations. (2nd January 2016) - Komocsar, Wendy J.; Blackbourne, Jamie L.; Halstead, Carolyn A.; Winstead, Colleen J.; Wierda, Daniel
Abstract: The potential immunotoxicity of tabalumab was assessed as a component of standard pre-clinical toxicology studies in cynomolgus monkeys. To evaluate potential tabalumab-associated immunosuppression after antigen challenge, cynomolgus monkeys were administered placebo control or tabalumab in three immunotoxicological safety studies. Study 1, a 4-week pilot study, evaluated biweekly intravenous (IV) control, and 0.3, 1.0, 5.0, and 15.0 mg/kg tabalumab doses. Study 2 evaluated IV control, and 0.1, 1.0, and 30.0 mg/kg tabalumab doses biweekly for 6 weeks. Study 3 evaluated IV control and 0.1, 1.0, 30.0 mg/kg, and subcutaneous (SC) 30.0 mg/kg tabalumab biweekly for 6 months, with recovery (16 weeks) to monitor standard immunotoxicity endpoints. T-cell dependent primary and secondary antibody responses to tetanus toxoid antigen challenge (4-week and 6-week studies) or keyhole limpet hemocyanin (KLH; 6-week and 6-month studies) were evaluated as a measure of immunocompetence, together with quantitation of T- and B-cell subsets. In addition, anti-tabalumab antibody formation (6-week and 6-month studies) was assessed. The results indicated that, despite expected decreases in circulating B-cell populations, no changes in follicle histopathology or organ weights, except decreases in spleen weight (after 6-months of 30 mg/kg IV/SC treatment only), were attributed to tabalumab. Non-adverse microscopic decreases in size or number of germinal centers in spleen, mesenteric, and mandibular lymph nodes occurred, but without an effect on antibody responses to KLH or tetanus. At 16-weeks recovery, microscopic compound-related changes observed after 6 months of treatment were completely reversed (0.1 mg/kg group) and partially reversed (1.0 and 30.0 mg/kg groups), while peripheral blood B cells remained 66–72% reduced from baseline. Despite reduced germinal centres in lymphoid organs, and reductions in circulating B cells, T-cell-dependent humoral immunity was maintained following tabalumab administration in three safety studies in cynomolgus monkeys.